2018
DOI: 10.7454/jki.v21i2.570
|View full text |Cite
|
Sign up to set email alerts
|

Hypnoparenting Effects Towards Fatigue as an Impact of Chemotherapy Among Pediatric Patients With Acute Lymphoblastic Leukemia

Abstract: The management of fatigue among pediatric patients with lymphoblastic leukemia does not become a priority apart from the cancer management itself. Hence, it is necessary to put an attention towards this issue by giving another complementary therapy for the patient called hypnoparenting. By implementing hypnoparenting will decrease the level of fatigue because of the chemotherapy process. Therefore the purpose of study was to investigate the effect of hypnoparenting towards fatigue prevalence as an impact of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…The next research is about the effect of HypnoParenting on fatigue in ALL children due to chemotherapy. The study was conducted at Ulin Banjarmasin Hospital by researcher Anggraini [14]. From this study, it was concluded that HypnoParenting intervention was effective in reducing the effects of chemotherapy, which is fatigue.…”
Section: Mind-body Spirit Therapiesmentioning
confidence: 99%
“…The next research is about the effect of HypnoParenting on fatigue in ALL children due to chemotherapy. The study was conducted at Ulin Banjarmasin Hospital by researcher Anggraini [14]. From this study, it was concluded that HypnoParenting intervention was effective in reducing the effects of chemotherapy, which is fatigue.…”
Section: Mind-body Spirit Therapiesmentioning
confidence: 99%
“…In the 25 studies in this review, 23 studies were quantitative design, and two studies were qualitative design. The quantitative studies comprised 7 cross sectional study (Agnes et al, 2019;Devi & Allenidekania, 2019;Fadhilah & Allenidekania, 2019;Mostert et al, 2008;Novrianda & Khairina, 2015;Rata et al, 2017;, 10 descriptive retrospective cohort study (Alfina et al, 2011;Hapsari et al, 2013;Mostert et al, 2013;Permatasari et al, 2009;Simanjorang et al, 2013;Tehuteru, 2011;Widiaskara et al, 2016;Wijayanti & Supriyadi, 2017), 2 retrospective Case Control Study (Agnes et al, 2019;Hapsari et al, 2013), 3 quasiexperimental study (Anggraini, 2018;Kulsum et al, 2017;Novrianda & Khairina, 2015), and one randomized clinical trial (Sitaresmi et al, 2013) (table. 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For example, some studies reported that the survival rate as the outcome of treatment was low in all hospitals setting (Alfina et al, 2011;Mostert et al, 2010;Permatasari et al, 2009;Simanjorang et al, 2013;Sitaresmi et al, 2013;Tehuteru, 2011;Wijayanti & Supriyadi, 2017;Yakin et al, 2017). The most common adverse effects of chemotherapy and experienced by more than 50% of children, including fever, infection, bleeding alopecia, loss of appetite, fatigue, pain, fatigue, and mucositis (Agnes et al, 2019;Anggraini, 2018;Devi & Allenidekania, 2019;Fadhilah & Allenidekania, 2019;Widiaskara et al, 2016). Based on the side effects of chemotherapy experienced by children, infection is the most common cause of child deaths .…”
Section: Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini sesuai dengan pendapat (Astuti, Sofiyanti, & Setyowati, 2019) yang mengatakan bahwa hypnoparenting merupakan teknik yang sangat bermanfaat untuk meningkatkan kecerdasan spiritual dan kualitas komunikasi orang tua dan anaknya. (Anggraini, 2018) menambahkan bahwa hypnoparenting dapat meningkatkan tingkat relaksasi seseorang. Hypnoparenting bertujuan untuk memberi kemudahan kepada orang tua dalam memberikan arahan (pembinaan) kepada anakanya tanpa adanya paksaan.…”
Section: Pendahuluanunclassified